Explorasi Dinamika Psikologis Dampak Celebrity Worship pada Remaja yang Memiliki Fan-Account - Aurellia, Patricia; Budiarto, Yohanes (AHKAM, 2024)
The rapid development of technology and easy access to social media platforms have strengthened the relationship between fans and celebrities, creating a strong emotional bond, known as the phenomenon of celebrity worship. This study aims to identify the impact of celebrity worship on adolescents who have fan accounts on social media, using qualitative survey methods and mixed-method analysis. Data were obtained from 123 adolescent participants (12-18 years old) who actively idolize celebrities and have fan accounts. This study provides different results from previous literature studies on the impact of celebrity worship. The results showed that the majority of participants reported positive impacts, such as increased motivation, positive emotions, and self-improvement in the affective and behavioral dimensions. On the other hand, negative impacts were also found, such as decreased emotional regulation, decreased self-control, and tendencies towards violence on the internet. Cognitive impacts showed increased mental resilience and emotional regulation in most fans. Although celebrity worship can have a positive influence in terms of motivation and self-quality, this phenomenon can also be at risk of reducing mental health and triggering conflict between fans.